Mistura de quatro ondas na propagação de pulsos ópticos ultra-curtos em fibras com dispersão decrescente para sistemas WDM - Fernandes, Lorenna Maia (2005)
This dissertation will study the behavior of the propagation of three types of optical pulses (Solitons, Quasisolitons and Gaussianos, short ultra in the area of 1.55μm) and their efficiencies of conversion in the generation of pulses through the non linear phenomenon of four waves mixture (FWM) in a common fiber and in fibers with decreasing dispersion in systems multiplexados by wavelength division (WDM). Six different dispersion profiles were used during the simulations of propagation of the pulses through 100km of fibers: Constant, Linear, Logarithmic, Gaussiano, Exponential and Hyperbolic. The analysis of the results concluded that the efficiency of conversion declines when he/she increases the separation of the channels independently of the profile. The Hyperbolic profiles presented the largest efficiency when in the separation of channel of 0.2nm, being of approximately 1000 times larger in magnitude if compared to the other profiles Constant, Lineal and Logarithmic. In the pulse Gaussiano all profiles presented the same efficiency starting from the separation of 0.675nm, except for the Hyperbolic profile. While in the Soliton and Quasisoliton pulses, the Exponential profiel also presents such exception. The conversion efficiency along the length of the fiber was analyzed for the three types of pulses for each one of the six profiles. For all of the types of pulses the profiles that presented larger efficiency in decreasing order were, the Hyperbolic, the Exponential and Gaussiano. The other three, Constant, Lineal and Logarithmic, presented very close efficiencies for the three types of pulses. The presence of pulses generated by the instability modulacional for the three types of pulses in the profiles Constant, Lineal, Logarithmic, Gaussiano and Exponential was observed during the propagation. After travelling approximately 20Km the instability modulacional disappears in the first three profiles in all types of pulses while in the other two profiles the phenomenon stays until the end of the propagation in most of the cases. There was an increase of the efficiency of the conversion of the pulse in the channel 3 when of the increment of the potency of the incident pulses in the channels 1 and 4 in all the three types of pulses in each one of the six profiles. The analysis of the compression factor indicated that the pulse generated in the channel 3 by mixture of four waves (FWM) and the incident pulse in the channel 4 always presented compression during the propagation. The incident pulse in the channel 1 also presented compression in most of the profiles and in the Hyperbolic profile it presented strong enlargement attributed to the loss of energy. In the pulse generated in the channel 3 in all of the cases a strong oscillation was observed in the first 20 Km while in the Soliton and Quasisoliton pulses the Gaussian profile presented an abrupt variation after traveling 60 Km and being stabilized before the end of the propagation. This analysis concludes that the control of the efficiency of conversion and of the compression factor in the generation of mixture of four waves is made possible by the use of fiber optic with decreasing dispersion.